If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 630 = 7x * 6 Reorder the terms for easier multiplication: 630 = 7 * 6x Multiply 7 * 6 630 = 42x Solving 630 = 42x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42x' to each side of the equation. 630 + -42x = 42x + -42x Combine like terms: 42x + -42x = 0 630 + -42x = 0 Add '-630' to each side of the equation. 630 + -630 + -42x = 0 + -630 Combine like terms: 630 + -630 = 0 0 + -42x = 0 + -630 -42x = 0 + -630 Combine like terms: 0 + -630 = -630 -42x = -630 Divide each side by '-42'. x = 15 Simplifying x = 15
| 0.7(3x-5)=14.5-3.9 | | y-5=2(X+6) | | 13/2x-32= | | 4D-4=5D+8 | | 7=3+2z | | 9p+6=-9-p | | 5a-3=4a-3 | | 9(x+1)(x+1)=(x+2)(x+2) | | -3n-3=9 | | -11(3/2)(.12)-12))= | | 3xy-5a=4c | | 3n-18/5=5/7 | | -5=3+2y | | -y+276=32 | | 12(-12)= | | 6-12=z/-8 | | 0=(2x^3)-8x-2x^3 | | 17+d=-7d-7 | | 7x+51=2x-13 | | 25+6w=11w | | 11=5.5x+258 | | 4-3[x+2]-2[x-4]+8=1 | | w=24-2w | | n/9=20 | | (2^2x^2/xy^3)^2 | | 2+20x=19x-11 | | 95=.05s^2+1.1s | | -11(3/2) | | 4v+24=10v | | 52+2x=90 | | y=258+60.5x | | 5x/-11=-54 |